2013
DOI: 10.1111/jocn.12291
|View full text |Cite
|
Sign up to set email alerts
|

The effect of injection duration and injection site on pain and bruising of subcutaneous injection of heparin

Abstract: This study proposed a suitable method for subcutaneous heparin injection in order to reduce pain and bruising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
1
26
2
5
Order By: Relevance
“…Our study shows that approximately 9 of 10 needle insertions in the abdomen and 8 of 10 needle insertions in the thighs were associated with acceptable levels of pain. Nevertheless, injections administered in the thighs caused significantly more pain than injections administered in the abdomen, which is in line with findings from other studies .…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that approximately 9 of 10 needle insertions in the abdomen and 8 of 10 needle insertions in the thighs were associated with acceptable levels of pain. Nevertheless, injections administered in the thighs caused significantly more pain than injections administered in the abdomen, which is in line with findings from other studies .…”
Section: Discussionsupporting
confidence: 91%
“…For injection volumes >1 mL, there are concerns of increased pain upon injection, high subcutaneous back pressure, site leakage, and injection site reactions. [14][15][16][17][18][19][20][21] Studies investigating subcutaneous rehydration and subcutaneous immunoglobulin replacement therapy have shown that the subcutaneous tissue can accommodate volumes >1 mL with good tolerability. [22][23][24][25][26][27] Hizentra (CSL Behring, Kankakee, IL), Gammunex-C (Grifols Therapeutics, Research Triangle Park, NC), and Gammagard Liquid (Baxter, Westlake Village, CA) are commercially available immunoglobulin replacement products in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…These differences were not statically significant. Overall, the mean and standard deviations of pain immediately after the procedure in patients with and without previous arterial puncture were 4.27 (1.94) and 3.35 (1.44), respectively (p<0.05). Also, all patients in the treatment group who had previous arterial punctures declared that the use of cold packs were effective in reducing the pain of arterial puncture.…”
Section: Resultsmentioning
confidence: 97%